BHAKTI MARGA YOGA: IMPLEMENTASI DALAM KEHIDUPAN PRIBADI DAN SOSIAL - I Gusti Agung Dharmawan (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2020)
Bhakti Marga Yoga is the path most people find easiest to practice compared to the other four paths. However, the path is sometimes not understood comprehensively so that some people carry it out only as a habit, not as a form of approaching oneself and the way to achieve union with Brahman and its practice is limited to bhakti service in the form of worship/ritual to God and sometimes ignore Bhakti to fellow and nature. Bhakti Marga Yoga means approaching God by fully surrendering oneself to God with full love and pure love. Implementation of Bhakti Marga Yoga, that is: 1). Studying Religi and Hinduism Susastra; 2). Performing worship to God; 3). Religious ceremony; 4). Community Service (Ngayah); 5). Bhakti to Catur Guru.